2019
DOI: 10.3389/fnins.2019.00340
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function in Acquired Bilateral Vestibulopathy: A Cross-Sectional Study on Cognition, Hearing, and Vestibular Loss

Abstract: Background Several studies have demonstrated cognitive deficits in patients with bilateral vestibulopathy (BVP). So far, little attention has been paid to the hearing status of vestibular patients when evaluating their cognition. Given the well-established link between sensorineural hearing loss (SNHL) and cognitive decline and the high prevalence of SNHL in BVP patients, it is therefore uncertain if the cognitive deficits in BVP patients are solely due to their vestibular loss or might be, partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 60 publications
(100 reference statements)
5
61
2
Order By: Relevance
“…Imbalance and oscillopsia were the most commonly reported symptoms. This is congruent with previous literature [8,9]. However, since these symptoms are part of the diagnostic criteria for BV [6], the found percentages could (partially) reflect a possible selection bias.…”
Section: Symptomssupporting
confidence: 92%
See 1 more Smart Citation
“…Imbalance and oscillopsia were the most commonly reported symptoms. This is congruent with previous literature [8,9]. However, since these symptoms are part of the diagnostic criteria for BV [6], the found percentages could (partially) reflect a possible selection bias.…”
Section: Symptomssupporting
confidence: 92%
“…This should be acknowledged, since clinical experience and earlier performed retrospective studies showed a wide variety of symptoms and consequences [8]. For example, BV patients reported negative impact on physical and social functioning, and compromised cognitive abilities as well [3,4,[8][9][10][11][12][13]. Therefore, it is important to investigate this whole spectrum of symptoms and consequences, especially when developing candidacy criteria and/or outcome measures for therapeutic interventions in this patient population [14].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of cognitive impairment on VR outcomes is not well understood, but a recent report suggests that patients with bilateral vestibular loss have attention impairments. 93 Although cognitive impairment may not alter the physiology of vestibular compensation, it could impact recovery if it interferes with a person's ability to comply with exercises and recall what he/she has previously learned in therapy (so-called carry-over effect). Micarelli et al 94 investigated posturography and self-report outcomes in older adults with unilateral vestibular hypofunction who had mild cognitive impairment (MCI) or Alzheimer's disease (AD).…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…Compared with literature, this prevalence was relatively high. 34 Vice versa, more than half of patients with hearing loss (26-80 dB HL of better ear) presented with vertigo and abnormal vestibular test results (including caloric irrigation and vestibular-evoked myogenic potential (VEMP) testing). 35 This underpins the importance of assessing both hearing and vestibular function in these patient groups.…”
Section: Open Accessmentioning
confidence: 99%